VD_FINDINFO HC / 2010 / 408 vom 3. August 2010 - VD Tribunal cantonal (2010)
SUSPENSION DE LA PROCÉDURE, DÉCISION INCIDENTE, LITISPENDANCE, INTERNATIONAL, CONVENTION DE LUGANO | 21 CL, 6 ch. 3 CL, 124a CPC, 451 ch. 7 CPC, 452 al. 1ter CPC, 452 al. 2 CPC, 465 al. 1 CPC